Pengaruh Jumlah Saham Beredar, Harga Saham dan Presentase Saham Publik Terhadap Likuiditas Saham Perusahaan Yang Listing di JII Periode 2013 - Ira Erlinawati; Imron Mawardi (Jurnal Ekonomi Syariah Teori dan Terapan, 2015)
The increase on market capitalization, number of traded shares, frequency of stocks trading and stocks price index influence the stock liquidity. Stocks which have a high market capitalization and that index prices always increase reflected in the Jakarta Islamic Index (JII). It is because the majority shares on JII are member of LQ45 which have a big market capitalization and good track record. Therefore interesting to do research to see the effect of the number of shares, the stock price and the percentage of public stock to the stock liquidity of listed companies on JII. The approach used in this research is quantitative with multiple linear regression analysis technique. The independent variables are the number of shares, the stock price and the percentage of public stock, and the dependent variable is stock liquidity. The samples are 30 listed companies on JII of period 3 June to 29 November 2013. Simultaneously, the number of shares, the price stock and the percentage of public stock have significant effect on stock liquidity. Partially, only the price stock and the percentage of public stock that affect on stock liquidity.